Studies on the syntheses of pyrroles and triazoles from vinyl azides and 1,3-dicarbonyl compounds - Ng, Eileen Pei Jian (2013)
Nitrogen-containing heterocycles (azaheterocycles) are compounds of great significance in the pharmaceutical industry because of their versatile biological activities. Members of this family have also been widely found in a myriad of natural products as they make up the dominant subunits oflife.